Dissolution of Monte Fresco phosphate rock and their effects on phosphorus fractionation in Venezuelan soils - López-Hernández, Danilo (Revista de la Facultad de Agronomía de la Universidad del Zulia, 2022)
Incubation tests analysed the reaction of Monte Fresco phosphoric rock (PR) with nine Venezuelan soils representative of different agro-ecological conditions, and contrasting physical-chemical and mineralogical characteristics linked to the PR dissolution process. The soils presented different capacities to dissolve the PR; response, generally associated with its intrinsic characteristics. The highest PR dissolution value (ΔP) was found in the soil Iguana (50 mgP.kg-1 soil), soil with appropriate properties to induce this process: acidic pH and low content of total and available P, followed with intermediate values (7-22 mg P.kg-1 soil) for Barinas and Casupal with acidic pH and moderate content of total P. The other soils had low dissolution rates (1.4-3.0 mg P.kg-1 soil) and higher P content. Finally, Veguitas and Bajo Seco soils with pH ≥5.6, and high total and available P contents and exchangeable calcium, showed no PR dissolution. The process of dissolving the PR during incubation is complex, it is activated with the presence of hydrogen ions around the fertiliser but can be affected by enzymatic and microbiological events as PR interacts with the soil, so that the dynamics of PR dissolution fluctuate.